KOLABORASI REGIONAL DALAM MENJAGA KEAMANAN MARITIM : STUDI KASUS PERAN AMF DI ASIA TENGGARA - Aretha Michellia, Ananda; Burhanuddin, Agussalim (JIMR : Journal Of International Multidisciplinary Research, 2024)
Maritime security is an important issue that must continue to be studied along with the development of science and technology. The misuse of technology in the maritime sector makes Southeast Asia, a region dominated by water, receive threats in maritime security. This research examines the types of transnational crime, how the ASEAN Maritime Forum (AMF) plays a role in maintaining maritime security stability in ASEAN, and the factors behind the AMF's failure to be effective in ASEAN. This research uses a qualitative method by constructing the reality behind the AMF's role in maintaining maritime security stability in Southeast Asia. The results of this study show that transnational crimes in Southeast Asian waters are increasing, and the AMF has failed to realize its goal of eradicating threats to maritime security. The failure of the AMF to maintain maritime security stability in Southeast Asia is expected to be evaluated, and the implementationof existing policies is expected to be improved.